Υπολογιστική ρευστοδυναμική μελέτη του σημείου πρόσβασης αρτηριοφλεβικού μοσχεύματος σε αιμοκαθαιρομένους ασθενείς - Σιούκας, Παντελάκης (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Based on the increasing incidents of patients with chronic kidney disease and the limited number of kidney transplants make hemodialysis the principal method that substitutes functions of the kidney. The process of hemodialysis takes place outs of the human body, so it’s necessary to have a permanent access point and any vascular access to ensure the continuous and uninterrupted blood during dialysis. One of the major problems that determine rejection of the arteriovenous graft, according to studies is the blockage of vascular access due to clots (Thrombosis). The purpose of this study is the creation of a realistic model of the arteriovenous graft, which is taken by MRI images when patients are on a dialysis session, and then the simulation and analysis of the flow field of blood in this model with the use of Computer Fluid Dynamics methods. The study of the flow field concerns the distribution of velocities in the entire model of AVG, also we seek areas with recirculation in the flow, the distribution of pressure and shear stress on the arteriovenous graft wall.
Keywords: Thrombosis; Hemodialysis; Arteriovenous graft; Computational fluid dynamics; Arteriovenous anastomoses; CFD; Imaged based CFD; Θρόμβωση; Υπολογιστική ρευστοδυναμική; Αρτηριοφλεβικό μόσχευμα; Αρτηριοφλεβική αναστόμωση; Αιμοκάθαρση